DUAL RECIPROCITY BOUNDARY ELEMENT METHOD (DRBEM) DENGAN PREDIKTOR-KOREKTOR UNTUK MASALAH INFILTRASI STASIONER PADA SALURAN DENGAN LAPISAN IMPERMEABEL DENGAN ROOT WATER UPTAKE - Irma Novalinda Nasution (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2019)
This study  aims to discussed  about Dual Reciprocity Boundary Element Method (DRBEM) with a predictor-corrector for steady infiltration problems with impermeabel layer with root water uptake in homogeneous soils. Steady infiltration in homogeneous soils is governed by Richard equation. This equation is transformed using a set of transformation including Khirchoff, dimensionless variabels and dimensionless parameters into a type of modified Helmholtz equation. Furthermore with DRBEM, numerical solution of modified Helmholtz equation obtained. The proposed method is tested on problem involved infiltration from rectangular and trapezoidal channels with impermeabel layer with root water uptake. Keyword : infiltration, root water uptake, modified Helmholtz equation, Richard equation, DRBEM